ELECTRONIC WORD OF MOUTH DAN PERCEIVED RISK : ANTECEDENT KEPUTUSAN PEMBELIAN - Intan Widhi Widhi Hapsari; Diesyana Ajeng Pramesti; Nur Hidayah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2022)
Electronic Word of Mouth currently is a way for people transform informations with others. There is Perceived Risk which must be considered. This study aims to examine the effect of Electronic Word Of Mouth, Persived Risk, on purchasing decisions in the Marketplace. The sample of this research is consumers who have made online purchases at Shopee in Magelang. The sampling method used purposive sampling with a total sample 100 respondents. Multiple linear regression using SPSS version 25.0 program used in statistical process. The results of this study indicate that partially and simultanoustly, Electronic Word of Mouth and Perceived Risk have a positive effect on purchasing decisions.